Social Sciences Driving Educational Policy and Curriculum Development - Björge Ríkeyi Ruögen; Stuart Jhon McNaughtona; Tan Cheng Han Shu; Monaqie M. G. Stricker; Carl Mark Anthony (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2024)
Social sciences play a strategic role in the development of educational policies and curricula aimed at creating an inclusive, relevant, and adaptive education system that responds to social changes. The background of this research is rooted in the need to understand how disciplines such as sociology, anthropology, and psychology can provide both theoretical and practical foundations for designing evidence-based educational policies. This study aims to analyze the contribution of social sciences in shaping educational policy and curriculum development, as well as identifying the challenges and opportunities present. The method used is library research with a descriptive-analytical approach. Data is gathered from primary and secondary literature, including academic books, journal articles, and policy documents from both national and international sources. The analysis is conducted through the synthesis of findings to produce a holistic overview of the relationship between social sciences, educational policy, and curriculum development. The results of the study show that social sciences contribute significantly to understanding social inequalities, building culturally relevant curricula, and designing educational policies that are responsive to societal needs. However, implementation is often hindered by the gap between theory and practice, resource limitations, and the influence of political agendas. This research concludes that integrating social sciences into education can enhance the quality of policies and curricula. Collaboration between academics, policymakers, and practitioners is necessary to optimize the contribution of social sciences to a more inclusive and sustainable education system.